A ladder channel composite molecular sieve adsorbent and preparation method thereof

By using different silicon-rich clay and molecular sieve ratios and the structural orientation of the additives, the A/X composite molecular sieve with step-by-step channels is constructed, which solves the problems of slow diffusion speed of existing molecular sieve adsorbents and poor shape selection effect of composite zeolites, achieving efficient adsorption separation and low production costs.

CN116474717BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210045613.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-15
Publication Date
2025-05-02
Estimated Expiration
2042-01-15

AI Technical Summary

Technical Problem

The existing molecular sieve adsorbents diffuse slowly in microporous channels, which affects the adsorption and separation efficiency. The shape selection effect and mechanical strength of composite zeolites are poor and the cost is higher.

Method used

Silicon-rich clay is used as the binder, and the silicon-aluminum ratios of A-type molecular sieve and X-type molecular sieve are different and the structural orientation of the additives, the low-temperature aging and transformation process are used to convert the binder into an X-type molecular sieve to construct an A/X composite molecular sieve with step-by-step pores.

Benefits of technology

The rapid absorption/desorption step of adsorbent is achieved, the diffusion rate and selectivity are improved, and the production cost is reduced, thereby avoiding the defects of the single-channel structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a composite molecular sieve with "small micropores-large micropores-mesopores" stepped channels and a preparation method thereof. The present invention uses silicon-rich activated clay as a binder for preparing a molded adsorbent, and utilizes the difference in silicon-aluminum ratios between type A molecular sieves and type X molecular sieves, as well as the structural guiding effect of the auxiliary agent in the molded body, and through low-temperature aging and crystallization processes, the silicon-rich binder is converted to type X molecular sieve to the greatest extent, thereby obtaining an A / X composite molecular sieve with stepped channels. The A / X composite molecular sieve adsorbent prepared by the method of the present invention has high selectivity and a relatively high diffusion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a stepped channel adsorbent, and belongs to the field of adsorbent synthesis. Background Art

[0002] Molecular sieves have uniform and regular pore structure and large specific surface area. They are polar adsorbents and have stronger adsorption capacity for highly polar and unsaturated molecules. They also have strong adsorption capacity for some easily polarized non-polar molecules. Therefore, they are widely used in the field of adsorption. Generally speaking, molecular sieves are mainly composed of micropores. As the adsorption site of small molecules, micropores have a screening effect and are ideal for adsorption separation. However, when the micropores are too small, the diffusion rate of impurities in the micropores is slow, so it is not conducive to the occurrence of reactions from a kinetic point of view. The pores of type A molecular sieves are 4~5 angstroms, the silicon-aluminum ratio is 1, the content of cations outside the framework is the highest, the adsorption capacity and selectivity are high, while the pores of type X molecular sieves are ten-membered rings, the pore size is 7~10 angstroms, and they have a more unobstructed pore structure, but the shape selection effect, mechanical strength are poor and the price is higher. Composite zeolites have different properties from single zeolites. Therefore, how to design adsorbents that can achieve both screening functions and high diffusion rates has gradually attracted widespread attention.

[0003] CN 103253681A discloses a method for preparing Na-A / X or Na-A / X / P co-crystallized molecular sieves by hydrothermal synthesis of lithium slag. During the preparation process, except for lithium waste slag, no silicon or aluminum source is added, and the ratio of A, X and P type molecular sieves in the Na-A / X or Na-A / X / P co-crystallized molecular sieves can be obtained by changing the process conditions during the synthesis process.

[0004] CN102557067A discloses a method for preparing a low-silicon Na-A / X eutectic molecular sieve in a pure sodium aluminosilicate system, which is characterized in that no potassium raw material is used, which can reduce production costs and avoid the adverse effects of residual potassium ions in the zeolite on ion exchange performance.

[0005] Conventional co-crystallized molecular sieves are synthesized based on powder structures, and the resulting pore structures are uncontrollable. In addition, binders are introduced during the molding stage to destroy the eutectic structure. Therefore, the development of molded adsorbents with multi-level pores is of great significance for rapid adsorption and separation devices. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a composite molecular sieve adsorbent having a "small micropore-large micropore-mesopore" step-channel structure and a preparation method thereof. The present invention uses silicon-rich clay (silicon-aluminum ratio>1) as a binder to prepare a molded adsorbent, and utilizes the difference in silicon-aluminum ratios between type A molecular sieve and type X molecular sieve, as well as the structural guiding effect of the additive in the molded body, and through low-temperature aging and crystallization processes, the binder is converted to type X molecular sieve to the greatest extent, thereby constructing an A / X composite molecular sieve with a step-channel structure.

[0007] According to the first aspect of the present invention, the present invention provides a method for preparing a composite molecular sieve adsorbent having a "small micropore-large micropore-mesopore" stepped pore channel.

[0008] A method for preparing an A / X composite molecular sieve adsorbent with stepped pores comprises the following steps:

[0009] (1) taking 70-95 parts by weight of 4A molecular sieve, 5-25 parts by weight of silicon-rich activated binder and 6-15 parts by weight of auxiliary agent, mixing and kneading, forming, drying and low-temperature calcining to obtain an intermediate molded body;

[0010] (2) adding the intermediate molded body to an alkaline solution of a certain concentration and stirring evenly, aging at 40-50°C for 1-6 hours, and reacting at 60-85°C for 1-6 hours to convert the silicon-rich binder into an X-type molecular sieve;

[0011] (3) The intermediate obtained in step (2) is washed and then added to a calcium salt solution for calcium exchange reaction;

[0012] (4) After washing, drying and roasting are carried out to obtain the final product.

[0013] Furthermore, the silicon-rich binder in step (1) is generally selected from one or more of attapulgite, diatomite, and bentonite, and the silicon-rich activated binder refers to a binder with a silicon-aluminum ratio (i.e., SiO2 / Al2O3 molar ratio)>1. The activation temperature of the binder after high-temperature calcination activation is generally selected from 500~800℃, and the activation time is 2~10h. Preferably, the activation temperature is 550~650℃, and the activation time is 3~5h.

[0014] Furthermore, the auxiliary agent in step (1) can be selected from one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, sesbania powder, PEG, P123, and CTAB. The catalyst intermediate molded body can be a strip or spherical particle. Furthermore, the drying temperature in step (1) is 80-120° C., and the drying time is 6-24 hours.

[0015] Furthermore, the low-temperature calcination temperature is 150-550°C, and the calcination time is 1-6 hours. Preferably, the calcination temperature is 150-250°C, and the calcination time is 3-5 hours.

[0016] Furthermore, the alkali in step (2) can be one or both of potassium hydroxide and sodium hydroxide.

[0017] Furthermore, the concentration of the alkaline solution in step (2) is 0.4-1.0M.

[0018] Furthermore, the calcium salt in step (3) can be one or more of calcium chloride, calcium hydroxide, calcium nitrate, and calcium bicarbonate, the calcium salt concentration is 0.5-3M, the reaction temperature is 70-100°C, and the reaction time is 1-8h.

[0019] Furthermore, in step (4), the drying temperature is 80-150°C, and the drying time is 12-48 hours; the roasting temperature is 300-550°C, and the roasting time is 2-10 hours.

[0020] According to the second aspect of the present invention, the present invention provides an A / X composite molecular sieve adsorbent with stepped pores, which is prepared by the method described above.

[0021] The composite molecular sieve adsorbent prepared by the method of the present invention has two or more microporous and mesoporous structures at the same time. Among them, the small micropores are the part that actually plays a sieving role, and the large micropores also have adsorption capacity, but their selectivity is not as good as that of the small micropores. They play the role of mass transfer and adsorption separation in the adsorbent at the same time; the mesoporous part mainly provides a through channel for the adsorption separation process.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. According to the difference in silicon-aluminum ratio between type A molecular sieve and type X molecular sieve, the present invention adopts silicon-rich activated clay as a binder, utilizes the structural guiding effect of the additive in the molded body, and controls the crystallization conditions to convert the binder into type X molecular sieve to the greatest extent, while avoiding its conversion into type A molecular sieve, thereby forming a stepped pore channel with high dispersion, and realizing a rapid adsorption / desorption sequence of the adsorbent.

[0024] 2. By in-situ converting the binder in the A-type molded molecular sieve into the X-type molecular sieve, a "small micropore-large micropore-mesopore" pore structure can be formed, and no additional silicon source, aluminum source or additional steps are required, so that high-quality composite adsorbent products can be produced at a lower cost. The A / X composite molecular sieve adsorbent has high selectivity and a relatively high diffusion rate.

[0025] 3. The composite A / X molecular sieve with stepped pores provided by the present invention has both the adsorption capacity of the A-type molecular sieve and the advantages of the X-type molecular sieve, avoiding the defects of the single pore structure, and also providing stepped pores of different sizes. The pore diameter of the X-type molecular sieve is larger than that of the A-type molecular sieve. The pore structure of the composite molecular sieve can make up for the shortcomings of the A-type molecular sieve due to the small pores and slow diffusion rate. While ensuring the adsorption capacity and selectivity, it can increase the diffusion rate and realize the fast cycle pressure swing adsorption operation. DETAILED DESCRIPTION

[0026] The technical content and effects of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0027] Example 1

[0028] The silicon-rich binder (silicon-aluminum ratio = 1.4) was placed in a muffle furnace and calcined at 650°C for 4 hours to obtain an activated silicon-rich binder.

[0029] Take 90 parts by weight of 4A molecular sieve, 10 parts by weight of silicon-rich activated binder, 2 parts by weight of sesbania powder and 12 parts by weight of CTAB, mix them mechanically, and then form and dry them. After calcining at 180°C, an intermediate molded body is obtained. Add 10 parts by weight of 4A molecular sieve to 0.6M sodium hydroxide solution and stir evenly, age at 45°C for 6h, react at 75°C for 4h, and convert the binder into X-type molecular sieve under the structural guidance of CTAB. After washing, place the intermediate in 2.5M calcium salt solution and react at 85°C for 4h. After washing, dry and calcine at 400°C to obtain the final product, and its performance evaluation results are shown in Appendix 1.

[0030] Example 2

[0031] The silicon-rich binder (silicon-aluminum ratio = 1.25) was placed in a muffle furnace and calcined at 650°C for 4 hours to obtain an activated silicon-rich binder.

[0032] Take 85 parts by weight of 4A molecular sieve, 15 parts by weight of silicon-rich activated binder, 4 parts by weight of sodium carboxymethyl cellulose and 10 parts by weight of P123, mix them mechanically, and then mold and dry them. Then, calcine them at 250°C to obtain an intermediate molded body. Add 10 parts by weight of 4A molecular sieve to 0.8 M sodium hydroxide solution and stir evenly, age at 50°C for 2 hours, react at 80°C for 4 hours, and convert the binder into X-type molecular sieve under the structural guidance of P123. After washing, place the intermediate in 2.0M calcium salt solution and react at 80°C for 2 hours. After washing, dry and calcine at 350°C to obtain the final product, and its performance evaluation results are shown in Appendix 1.

[0033] Example 3

[0034] The silicon-rich binder (silicon-aluminum ratio = 1.15) was placed in a muffle furnace and calcined at 600° C. for 5 h to obtain an activated silicon-rich binder.

[0035] Take 80 parts by weight of 4A molecular sieve, 20 parts by weight of silicon-rich activated binder, 1 part by weight of sodium carboxymethyl cellulose and 5 parts by weight of PEG10000, mix them mechanically, and then mold and dry them. Then, calcine them at 150°C to obtain an intermediate molded body. Add 10 parts by weight of 4A molecular sieve to 0.4 M sodium hydroxide solution and stir evenly, age at 48°C for 2 hours, react at 70°C for 6 hours, and convert the binder into X-type molecular sieve under the structural guidance of PEG. After washing, place the intermediate in a 3M calcium salt solution and react at 75°C for 4 hours. After washing, dry and calcine at 500°C to obtain the final product, and its performance evaluation results are shown in Appendix 1.

[0036] Example 4

[0037] The silicon-rich binder (silicon-aluminum ratio = 1.1) was placed in a muffle furnace and calcined at 550°C for 5 hours to obtain an activated silicon-rich binder.

[0038] Take 70 parts by weight of 4A molecular sieve, 30 parts by weight of silicon-rich activated binder, 4 parts by weight of carboxymethyl cellulose and 8 parts by weight of CTAB, mix them mechanically, then mold and dry them, and calcine them at 200°C to obtain an intermediate molded body. Add 10 parts by weight of 4A molecular sieve to 0.8M sodium hydroxide solution and stir evenly, age at 50°C for 3h, react at 85°C for 1h, and convert the binder into X-type molecular sieve under the structural guidance of CTAB. After washing, place the intermediate in 2.0M calcium salt solution and react at 80°C for 4h. After washing, dry and calcine at 500°C to obtain the final product, and its performance evaluation results are shown in Appendix 1.

[0039] Example 5

[0040] The silicon-rich binder (silicon-aluminum ratio = 1.5) was placed in a muffle furnace and calcined at 650°C for 3 hours to obtain an activated silicon-rich binder.

[0041] Take 75 parts by weight of 4A molecular sieve, 25 parts by weight of silicon-rich activated binder, 4 parts by weight of sesbania powder and 4 parts by weight of CTAB, mix them mechanically, then mold and dry them, and calcine them at 230°C to obtain an intermediate molded body. Add 10 parts by weight of 4A molecular sieve to 1.0M sodium hydroxide solution and stir evenly, age at 45°C for 2h, react at 85°C for 2h, and convert the binder into X-type molecular sieve under the structural guidance of CTAB. After washing, place the intermediate in 2.0M calcium salt solution and react at 85°C for 1h. After washing, dry and calcine at 500°C to obtain the final product, and its performance evaluation results are shown in Appendix 1.

[0042] Comparative Example 1

[0043] The preparation and evaluation of the adsorbent are the same as those in Example 1, except that kaolin with a silicon-aluminum ratio of 1 is used as a binder to prepare a reference agent B1, and its performance evaluation results are shown in Appendix 1.

[0044] Comparative Example 2

[0045] The preparation and evaluation of the adsorbent were the same as in Example 1, except that a shaped molecular sieve was prepared with 13X molecular sieve as the main component to obtain reference agent B2, and the performance evaluation results are shown in Appendix 1.

[0046] In the embodiments and comparative examples of the present invention, the adsorption amount is the static adsorption amount of N2 measured by a volumetric adsorption instrument, and the intensity is measured by the GB / T 13550-2515 method.

[0047] Table 1 Adsorbent evaluation results

[0048]

Claims

1. A method for preparing an A / X composite molecular sieve adsorbent having a stepped pore channel, characterized in that: The steps include: (1) 70-95 parts by weight of 4A molecular sieve, 5-25 parts by weight of silicon-rich activated binder and 6-15 parts by weight of auxiliary agent are mixed and kneaded, molded, dried and low-temperature calcined to obtain an intermediate molded body; (2) adding the intermediate molded body to an alkaline solution of a certain concentration and stirring evenly, aging at 40-50°C for 1-6 hours, and reacting at 60-85°C for 1-6 hours to convert the silicon-rich activated binder into an X-type molecular sieve; (3) The intermediate obtained in step (2) is washed and then added to a calcium salt solution for calcium exchange; (4) After washing, drying and roasting are carried out to obtain the final product; Wherein, the silicon-rich activated binder is a binder having a silicon-aluminum ratio>1 and activated at 500-800°C; the auxiliary agent in step (1) is selected from one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, sesbania powder, PEG, P123, and CTAB; The conditions for the low-temperature roasting in step (1) are: the roasting temperature is 150-250°C, and the roasting time is 1-6 hours; the roasting temperature in step (4) is 300-550°C, and the roasting time is 2-10 hours.

2. The preparation method according to claim 1, characterized in that: The silicon-rich activated binder is selected from one or more of attapulgite, diatomaceous earth and bentonite.

3. The preparation method according to claim 1, characterized in that: The drying temperature in step (1) is 80-120°C and the drying time is 6-24h.

4. The preparation method according to claim 1, characterized in that: The alkali in step (2) is one or both of potassium hydroxide and sodium hydroxide.

5. The preparation method according to claim 1 or 4, characterized in that: The concentration of the alkaline solution in step (2) is 0.4~1.0M.

6. The preparation method according to claim 1, characterized in that: The calcium salt in step (3) is selected from one or more of calcium chloride, calcium hydroxide, calcium nitrate and calcium bicarbonate, and the concentration of the calcium salt solution is 0.5-3M.

7. The preparation method according to claim 1 or 6, characterized in that: The temperature of calcium exchange in step (3) is 70-100°C, and the reaction time is 1-8h.

8. The preparation method according to claim 1, characterized in that: The drying temperature in step (4) is 80-150°C and the drying time is 12-48h.

9. The A / X composite molecular sieve adsorbent with stepped pores obtained by any one of the preparation methods of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing low-silicon Na-A / X cocrystallization zeolite in pure sodium aluminosilicate system

    CN102557067A

  • Method for preparing Na-A / X or Na-A / X / P cocrystal molecular sieve through lithium slag hydrothermal synthesis

    CN103253681A

  • Secondary perforated molecular siever adsorbent and preparation process thereof

    CN1248487A